Development of a Paediatric Musculoskeletal Skills Workshop for Canadian Medical Students. (1st June 2016) - Chan, M; Rumsey, D; Ellsworth, J; Foster, H
Abstract: BACKGROUND: Musculoskeletal (MSK) complaints in children account for up to 30% of visits to general practitioners. Doctors who see children with MSK complaints are often not confident in assessing them and MSK exams are poorly documented in medical records. There has been little published literature describing the logistics of teaching MSK skills in a group setting (which is how medical students are commonly taught). At our center, no MSK examination skills were previously taught during the undergraduate paediatrics clerkship. OBJECTIVES: 1) To develop a hands-on, paediatric MSK workshop for medical students with direct observation and feedback. 2) To evaluate student/faculty satisfaction with the workshop. 3) To develop an MSK workshop protocol as a resource for medical educators. DESIGN/METHODS: A 1-hour interactive workshop was designed for students to practice the paediatric Gait, Arms, Legs and Spine (pGALS) screening MSK exam. Students are given pre-reading, videos and pGALS checklists. Workshops include live demonstrations and videos/images of abnormal MSK findings for pGALS practice. Students practice pGALS with their peers with staff supervision(up to 5 physicians present)and receive feedback. All students complete a post-workshop evaluation. Teachers also complete a post-workshop evaluation discussing what went well and areas for improvement. RESULTS: Workshops are delivered every 2 months for 25 students (5 iterations completed). Feedback has been positive (median rating 4.5 on a 5-point Likert scale) for all areas evaluated: objectives, handouts, preparation time, discussion, resources, etc. Comments include: "Helpful and applicable to personal clinical practice, " and, "The hands-on practice was really appreciated, as was the chance to get feedback." Workshops have been modified according to faculty/student evaluations, resulting in a workshop protocol (organizational template) for future workshop leaders including a teaching checklist, preparation timeline, and PowerPoint to be modified by instructors as they wish. CONCLUSION: The paediatric MSK workshop has been a welcome addition to our undergraduate paediatrics clerkship curriculum. We aim to further develop our workshop by explicitly including applied anatomy, e.g., land-marking for joints. We also aim to make our workshop protocol available on Paediatric Musculoskeletal Matters, www.pmmonline.org, as a resource for other medical educators. Further work will include evaluating its uptake, use and applicability by users in different contexts, and modifying it for different levels of learners, e.g., paediatricians.